2009
DOI: 10.1016/j.jhazmat.2008.11.039
|View full text |Cite
|
Sign up to set email alerts
|

The photooxidative destruction of C.I. Basic Yellow 2 using UV/S2O82− process in a rectangular continuous photoreactor

Abstract: The photooxidative decolorization of C.I. Basic Yellow 2 (BY2), was investigated using UV radiation in the presence of peroxydisulfate (S(2)O(8)(2-)) in a rectangular photoreactor at experimental condition. S(2)O(8)(2-) and UV-light showed negligible effect when they were used independently. Removal efficiency of BY2 was sensitive to the operational parameters such as initial concentrations of S(2)O(8)(2-), BY2, light intensity, flow rate and pH. The conversion ratios of BY2 at the volumetric flow rates of 330… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(61 citation statements)
references
References 18 publications
4
57
0
Order By: Relevance
“…These observations implied that UV-365 nm/S 2 O 8 2-process was associated with a higher degradation efficiency of PVA owing to the following mechanism (Hori et al 2005(Hori et al , 2007Lau et al 2007;Salari et al 2009;Criquet and Leitner 2009;Lin et al 2011). and it can directly degrade PVA in aqueous solutions (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations implied that UV-365 nm/S 2 O 8 2-process was associated with a higher degradation efficiency of PVA owing to the following mechanism (Hori et al 2005(Hori et al , 2007Lau et al 2007;Salari et al 2009;Criquet and Leitner 2009;Lin et al 2011). and it can directly degrade PVA in aqueous solutions (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, UV/S 2 O 8 2-process has been confirmed to be effective in degrading organic contaminants (Hori et al 2005(Hori et al , 2007Lau et al 2007;Salari et al 2009;Criquet and Leitner 2009;Lin et al 2011). For example, Lin et al (2011) found that phenol (0.5 mM) can be completely degraded within 20 min using UV/S 2 O 8 2-process with a UV wavelength of 254 nm and an S 2 O 8 2-concentration of 84 mM.…”
Section: Introductionmentioning
confidence: 99%
“…The solution becomes more and more impermeable to UV radiation. Peroxydisulfate can then only be irradiated by a smaller portion of UV light to form lower free active radicals and the decolorization efficiency decreases 12,32 . Also Figures 4 and 5 showed that the color removal efficiency increased with increasing the reaction time.…”
Section: Optimization Of the Operational Variablesmentioning
confidence: 99%
“…The USEPA has listed it under the secondary drinking water standards with a maximum concentration of 250 mg/l (1.43 mmol/ l), based on aesthetic reasons 9,12 . The main objective of the optimization in this work is to determine the optimum values of variables for photooxidative decolorization using UV/S 2 O 8 2-process, from the CCD model obtained using the experimental data.…”
Section: Optimization Of the Operational Variablesmentioning
confidence: 99%
“…However, since the reactions of peroxydisulfate are generally slow at normal temperature. The thermal or photochemical activated decomposition of S 2 O 8 2-ion to SO 4 -radical has been proposed as a method of accelerating the process [19,20], as summarized in the following reactions (Eqs. 1-12):…”
Section: Introductionmentioning
confidence: 99%